Analysis of Educational Values in Macapat Song Learning in Kindergarten - Joko Pamungkas; Ad Dieni Maulana Rizka (Return : Study of Management, Economic and Bussines, 2022)
Background: Early childhood learning cannot be equated with adults. So education observers continue to develop and innovate in learning for children. The macapat song is one of the innovations and developments of early childhood learning media which has been implemented in ABA Ngabean 2 Kindergarten. Aim: The purpose of this study was to determine the educational values ??in the learning of the macapat song in TK ABA Ngabean 2. The macapat songs that were implemented in learning were the Potong and Gambuh songs. Method: This research method uses descriptive qualitative analysis by using data from observations, interviews, and conducting group discussion forums. Value analysis is associated with character education values ??based on Permendikbudristek number 7 of 2022 concerning PAUD content standards. Findings: The results of this study indicate that the macapat song has educational values ??that are following children's learning competencies according to the ministry of education in Indonesia